Avaliação biomecânica de protetores bucais personalizados: análise laboratorial e dinâmica não-linear de impacto por elementos finitos - Veríssimo, Crisnicaw (2015)
The practice of contact sports is highly associated with the occurrence of dental injuries. Mouthguards have been widely used in order to reduce the harmful effects of these injuries. The aim of this study was to evaluate the biomechanical performance of custom-fitted mouthguards through strain-gauge test and nonlinear dynamic impact analysis by finite element method. This study was conducted through five specific objectives. Objective 1: to evaluate an experimental dentoalveolar model to assess the biomechanical behavior, expressed by the stresses and strains generated by the use of mouthguards and validation of experimental test by means of nonlinear dynamic finite element impact analysis. Objective 2: evaluate the stress and strain, shock absorption ability and displacement of EVA custom-fitted mouthguards in different thicknesses (2, 3, 4, 5 and 6 mm). Objective 3: To evaluate the influence of hard inserts on the pattern of stress and strain distributions, shock absorption ability and displacement of EVA custom-fitted mouthguards. Objective 4: To evaluate the influence of the antagonist contact on the pattern of stress and strain distributions, shock absorbing capacity and displacement of custom mouthguards EVA. Objective 5: associate the results found in the objectives 1, 2, 3 and 4 with a clinical case report of custom mouthguard compiled in a communication paper for Brazilian dental clinicians. The experimental methods used were the strain gauge method associated with impact test, tensile test for mechanical characterization of ethylene vinyl acetate (EVA), and nonlinear dynamic impact finite element analysis for evaluation of the stress and strain generated by the impact. In finite element analysis, the von Mises and Critical Modified von Mises criteria were used for stress assessment. Based on the results it was concluded that custom-fitted 8 mouthguards are capable of reduce the stress and strain levels in the tooth-bone complex during impact. Using Critical Modified von Mises criteria, was found that the horizontal impact and without mouthguards created a critical condition for tooth fracture in the palatal side of the tooth crown. The mouthguard presence decreases significantly this critical condition. In impact tests using the pendulum device and experimental dentoalveolar model (bovine), it was concluded that the different angles (90, 60 or 45º), impact object (baseball or metal ball) and the presence of mouthguard significantly influenced the stresses and strains generated during an impact. The 90° angle promoted higher strain values. Custom-fitted mouthguards have an impact absorption capacity reaching levels of 98% based on the strain gauge test and 95% by finite element analysis. The results of the strain gauge test validated the finite element models, therefore both methods are considered suitable for evaluation of mouthguards. Custom-fitted mouthguards should be made in thickness from 3 to 4mm. The insertion of hard material inside of the mouthguard (middle layer) is recommended because it reduces the mouthguard displacement without significant changes in the stress and strain. The mouthguard adjusted according to the patient\'s occlusion and antagonist contact decreases the displacement of the mouthguard during an impact. Finally, the clinician must focus on all these aspects during the preparation and orientation of the use of EVA custom-fitted mouthguards.